2018
DOI: 10.3390/app8091480
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Tunable Acoustic Metamaterials

Abstract: Acoustic metamaterial science is an emerging field at the frontier of modern acoustics. It provides a prominent platform for acoustic wave control in subwavelength-sized metadevices or metasystems. However, most of the metamaterials can only work in a narrow frequency band once fabricated, which limits the practical application of acoustic metamaterials. This paper highlights some recent progress in tunable acoustic metamaterials based on various modulation techniques. Acoustic metamaterials have been designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 154 publications
0
52
0
Order By: Relevance
“…Examples of metamaterials exhibiting equivalent tensorial densities are numerous and have been used extensively in the literature regarding metamaterials for controlling sound waves, for example in the context of transformation acoustics and cloaking ( [27][28][29][30]). For what concerns active modulation of the equivalent properties, interesting studies have also been reported [31] both theoretically and experimentally [32][33][34][35]. A way of implementing anisotropy in a modulated acoustic medium has also been recently introduced by Allam et al [36].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of metamaterials exhibiting equivalent tensorial densities are numerous and have been used extensively in the literature regarding metamaterials for controlling sound waves, for example in the context of transformation acoustics and cloaking ( [27][28][29][30]). For what concerns active modulation of the equivalent properties, interesting studies have also been reported [31] both theoretically and experimentally [32][33][34][35]. A way of implementing anisotropy in a modulated acoustic medium has also been recently introduced by Allam et al [36].…”
Section: Discussionmentioning
confidence: 99%
“…For the last 10 years, the new concepts of acoustic metamaterials, and maetasurfaces have dominated the field of acoustics due to their ability to manipulate acoustic waves as never before and reviewed elsewhere. 2,3,33,34 Periodicity-enhanced metamaterials and metasurfaces are artificial structures with acoustic properties not found in nature and have already been proven in room acoustics 34 and in traffic noise attenuation 2 but they have not been explored for aeronautical applications. 3 Due to the advancement in 3D printing and the capability of making complex structures, there is an increased demand for studying the behaviour of sound propagation for new applications.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical, numerical and experimental investigations on negative effective mass [16][17][18], double negativity [19], tunable absorption in and transmission through membrane-type acoustic metamaterials [20][21][22][23][24][25][26][27][28], broadband noise mitigation using metamaterial panels with stacked membranes [29], impedance mismatch-driven reduction in transmitted sound energy for structures with attached gas layers [30], acoustic barriers utilizing cellular [31] and flexible [32,33] sub-structures, coupled membranes displaying monopolar and dipolar resonances [34], absorption using degenerate resonators [35], and targeted energy transfer from an acoustic medium to a nonlinear membrane [36] as well as for seismic mitigation [37] have been reported. There have been several studies ranging from tunable structural-scale AM [38,39] to active AM designs [40] that have clearly demonstrated their unique advantages. Utilizing AM to develop practical solutions for low-frequency acoustic noise mitigation is seen to be an area of emphasis.…”
Section: Introductionmentioning
confidence: 99%